Eucalyptus plantations : (World Scientific, 2003)
The book contains papers presented at a meeting by eucalyptus experts, scholars, consultants and company managers from different countries and regions. The authors report: (1) the most recent advances in eucalyptus research from different perspectives — genetics, breeding, cultivation techniques, soil nutrition, plantation management, wood utilization, etc.; (2) the world-wide extension and development of the cultivated eucalyptus as a strategic forest tree with great economic, environmental and social significance; (3) plantation management merging ecological, environmental and legal concerns in operations practised by the private sector; (4) new approaches to utilization of eucalyptus woods. This book also represents a successful combination of academic research and practical operation in managing commercial eucalyptus plantations.